Manajemen strategi: pendekatan manajemen layanan dalam meningkatkan loyalitas nasabah pada bank syariah - choirina, rizqin mufidah (Maliki Interdisciplinary Journal, 2025)
Customer loyalty is a crucial factor in maintaining the sustainability and stability of financial institutions, particularly in Islamic banking, which is based on the principles of justice, trustworthiness, and honesty. In this context, a service management approach is a crucial strategy for building long-term relationships between banks and customers. By implementing service management that focuses on customer needs and satisfaction, Islamic banks can create a service experience that is not only high-quality but also aligned with Islamic values. This approach emphasizes the importance of professionalism, empathy, and the integration of spiritual values ​​into every aspect of service. Therefore, implementing orderly and sharia-compliant service management can strengthen customer trust, increase satisfaction, and ultimately foster ongoing loyalty to Islamic banks.